Proses Labeling PROSES LABELING PADA FIGUR PUBLIK: STUDI KASUS EKY PRIYAGUNG SEBAGAI ‘DUTA BROKEN HOME’ DI INSTAGRAM : STUDI KASUS EKY PRIYAGUNG SEBAGAI ‘DUTA BROKEN HOME’ DI INSTAGRAM - Sukron, Sandi; Ghassani, rizqi (UKRI, 2025)
Labeling is an aspect that arises from society's reaction to a person's behavior that is considered deviant. The labeling perspective emphasizes the interactionism approach by concentrating on the consequences of interactions between deviants and social control agents. This research using descriptive methods to find out how Eky Priyagung's broken home content on Instagram gave rise to a broken home ambassador labeling on Eky Priyagung. The data obtained in this research through direct interviews with Eky Priyagung's sources. The results of this study prove that the labels given by the public can influence how a person behaves, creates strategies, and takes advantage of opportunities, ultimately forming an influential figure in raising social issues.